An Andean‐type arc transferred into a Japanese‐type arc at final closure stage of the Palaeo‐Asian Ocean in the southernmost of Altaïds. (18th December 2019) - Tian, Zhonghua; Xiao, Wenjiao
Abstract : Permian progressive accretion or continental rift is a long‐term debate topic in the final evolution of the Altaïds or the Central Asian Orogenic Belt (CAOB). The Beishan orogenic collage in the southernmost part of the CAOB recorded the ultimate closure of the Palaeo‐Asian Ocean. In this paper, we present (a) field structural measurements/data or observations and fold geological maps in the Liuyuan Basin, (b) geochronological results to rocks on the Shibanshan arc and in the Liuyuan Basin, and (c) geochronological and regional geological data collected around the Liuyuan area, in order to investigate the tectonic setting and evolution of the Liuyuan Basin, and finally discuss the termination of the Palaeo‐Asian Ocean. We notice that (a) rocks cropping out on both sides of the Liuyuan Basin have similar petrological and geochronological feature, which are probably from one ancient terrane, (b) sediments and volcanic rocks in the Liuyuan Basin formed in an arc‐related basin within an extensional deep to semi‐deep water setting or in a limited oceanic basin, and (c) at least two stages of folding could be recognized in the Liuyuan Basin; the age of this progressive deformation was constrained by the maximum depositional age of basinal sediments and undeformed or weakly deformed stitching plutons, which is variable from 275 to 217 Ma; orogenesis therefore was related to arc‐related accretion rather than a rift open‐close process in Late Permian to Early Triassic. Finally, we conclude that (a) the Liuyuan Basin is a back‐arc basin, not a rift basin or lake, (b) final closure of the Palaeo‐Asian Ocean was from Late Permian to Triassic, and (3) an Andean‐type arc transferred into a Japanese‐type arc at the final closure of the Palaeo‐Asian Ocean in the southernmost part of the CAOB. Last but not the least, we further speculate that eclogites developed in the Shibanshan arc were emplaced to the Beishan orogenic collage via a destroyed back‐arc basin.